Nilai-Nilai Pendidikan Islam Berbasis Kearifan Lokal dalam Novel Ronggeng Dukuh Paruk Karya Ahmad Tohari - Okti Nur Aminah; Mawi Khusni Albar (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
Islamic education based on local wisdom is an important component in the world of education today because humans not only need knowledge but also spiritual strength in a personality full of wisdom, good value, embedded and followed by community members which is then reflected in words, deeds, and feelings related to God, self, fellow humans. Education can be obtained from anywhere. One of them is through quality and quality literary works, namely the novel Ronggeng Dukuh Paruk by Ahmad Tohari. This study aims to determine the values ​​of Islamic education based on local wisdom in the novel Ronggeng Dukuh Paruk by Ahmad Tohari. This research is a type of library research research with a library approach. The primary data source is the novel Ronggeng Dukuh Paruk by Ahmad Tohari and other related sources. The data collection method used documentary studies with content analysis techniques. The results of the study concluded that the values ​​of Islamic education based on local wisdom contained in the novel Ronggeng Dukuh Paruk by Ahmad Tohari were the value of aqidah / faith education, the value of worship education, the value of moral education and the value of social education.